Can the external masculinization score predict the success of genetic testing in 46,XY DSD? - Ruthie Su; Margaret P. Adam; Linda Ramsdell; Patricia Y. Fechner; Margarett Shnorhavorian (AIMS Genetics, 2015)
Genetic testing is judiciously applied to individuals with Disorders of Sex Development (DSD) and so it is necessary to identify those most likely to benefit from such testing. We hypothesized that the external masculinization score (EMS) is inversely associated with the likelihood of finding a pathogenic genetic variant. Patients with 46,XY DSD from a single institution evaluated from 1994-2014 were included. Results of advanced cytogenetic and gene sequencing tests were recorded. An EMS score (range 0-12) was assigned to each patient according to the team's initial external genitalia physical examination. During 1994-2011, 44 (40%) patients with 46,XY DSD were evaluated and underwent genetic testing beyond initial karyotype; 23% (10/44) had a genetic diagnosis made by gene sequencing or array. The median EMS score of those with an identified pathogenic variant was significantly different from those in whom no confirmed genetic cause was identified [median 3 (95% CI, 2-6) versus 6 (95% CI, 5-7), respectively (p = 0.02)], but limited to diagnoses of complete or partial androgen insensitivity (8/10) or 5-reductase deficiency (2/10). In the modern cohort (2012-2014), the difference in median EMS in whom a genetic cause was or was not identified approached significance (p = 0.05, median 3 (95% CI, 0-7) versus 7 (95% CI, 6-9), respectively). When all patients from 1994-2014 are pooled, the EMS is significantly different amongst those with compared to those without a genetic cause (median EMS 3 vs. 6, p < 0.02). We conclude that an EMS of 3 or less may indicate a higher likelihood of identifying a genetic cause of 46,XY DSD and justify genetic screening, especially when androgen insensitivity is suspected.